STRATEGI PENCEGAHAN STUNTING MELALUI MPASI ‘SKENA’ DI LIPRAK KIDUL BANYUANYAR PROBOLINGGO - Putri, Arsyida Alfianti; Maulana, Safrizal Bangkit; Charits, Achmad Zuhri Al; Febriyanti, Inka Ayu; Atika, Meilani Fara; Mugiyati, Mugiyati (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a severe chronic nutritional problem that negatively affects children's growth and development so that the appropriate and sustainable nutrition interventions are needed. This research examines the strategy of children's nutrition through the 'SKENA' (Healthy, Creative, and Tasty) MPASI cooking demonstration as an effort to prevent stunting in Liprak Kidul Village. The method used in this research is PAR (Participatory Action Research) which requires researchers to be actively involved in solving humanitarian problems, such as mapping, transect, approach to the community, preparation of work programs, contacting related parties who will be invited to work together in the work program. The results of this activity showed an increase in mothers' understanding of the importance of balanced nutrition for children and their ability to prepare complementary foods that meet nutritional standards. In addition, this activity also encourages the active role of families in supporting the fulfillment of child nutrition. Hopefully, through this intervention, the stunting rate in Liprak Kidul Village can be significantly reduced. Thus, the 'SKENA' complementary food cooking demonstration can be an effective nutrition intervention model that can be adopted by other villages in stunting prevention efforts.